Project Management: Enhancing Company Resource Efficiency and Effectiveness - Winanto, Sujoko (SEAN Institute, 2024)
Project management represents a strategic endeavor aimed at enhancing the efficiency and effectiveness of a company. As technology evolves, it becomes imperative for companies to adapt to the significant changes occurring in the business landscape. This study seeks to provide a comprehensive conceptual explanation of project management. Conducted as a literature review, this paper analyzes various sources from journals, books, and websites that delve into the conceptual aspects of project management. Data collection for this paper is primarily based on documentation, including articles and books, and employs content analysis to analyze descriptive literature data or scientifically analyze premises conveyed. The data analysis methods employed are deductive, inductive, and comparative in nature. The key findings of this study indicate that project activities are temporary endeavors with defined resource allocations, aimed at accomplishing predetermined tasks within a specified timeframe. Project management entails planning, organizing, leading, and controlling company resources to achieve short-term objectives. While this paper shares similarities with others in discussing project management conceptually, it distinguishes itself by providing accompanying methodologies geared towards enhancing the efficiency and effectiveness of company resources in project management